Identification of physical and engineering properties of modified sand brick using coconut shell as cement replacement - Amar Sulaiman (School of Environmental Engineering, University Malaysia Perlis, 2013)
This research more focuses on producing the new environmental friendly product for construction industry. This will be one of the efforts to reduce the environmental pollution.